IMPLEMENTASI BIMBINGAN KARIER DALAM MENGOPTIMALKAN BAKAT SISWA MELALUI PEMBELAJARAN SENI BUDAYA di SDS TARBIYATUL ISLAM SAMBAS - Patriana Patriana (CV. ADIBA ASIHA AMIRA, 2024)
Career guidance in schools is an effort to help individuals or students understand and make broad use of the educational, position and personal opportunities that students have or can develop and as a form of systematic assistance to be able to obtain good adjustments to school, students and their lives. The implementation of career guidance in learning arts and culture and skills consists of several methods that have been implemented by the supervising teacher. Some of these methods have been implemented effectively, students' responses to several methods provided by the teacher have been good. Students are not bored with just sitting there. The aim of implementing career guidance in class IV is to further optimize and find out the interests and talents of each student in learning arts and culture and skills. All students must be able to know their interests and talents so that they can be further developed and as a starting point for entering the next level of school.